Introduction and diffusion of cassava in Africa: IITA research guide, No. 49 - Carter, S.; Fresco, Louise O.; Jones, P.; Fairbairn, J. (1997)
From the 15th to the 17th centuries, Portuguese explorers established forts, trading stations and settlements on the Mrican coasts and nearby islands. Prior to 1600 they began to introduce cassava at these points. From there it was diffused by Mricans, to reach many parts of the interior over the space of two to three hundred years. Cassava is now found in almost all parts of tropical Africa where conditions are suitable for its cultivation. In the course of its spread across the continent, cassava has replaced traditional staples in diverse parts of tropical Africa, and its social and environmental impact is considerable, although still not fully understood. It is therefore of vital importance to our understanding of contemporary African agricultural transformations to explain the reasons for its rapid adoption.